EFFECT OF HYPERBARIC OXYGEN THERAPY ON FASTING BLOOD GLUCOSE AND INSULIN RESISTANCE - Levent Demir; Şamil Aktaş; Nurdan Gül; Bengüsu Mirasoğlu; İlhan Satman; Mustafa Avcı (İstanbul Tıp Fakültesi Dergisi)
Objective: The subject of this study was to investigate the effect of hyperbaric oxygen (HBO2) therapy on fasting blood glucose levels and insulin resistance. The study investigated whether HBO2 therapy is effective in reducing peripheral insulin resis tance in patients with and without Diabetes Mellitus (DM) Material and Methods: The study included 27 patients with and without DM who received hyperbaric oxygen therapy at a pres sure of 2.4 ATA for 120 min per session, with 5-min air breaks ev ery 25 min, one session per day, five days a week, for 20 sessions. Patients were divided into two groups: those without DM and those with DM. Of the patients, 15 were without DM, while 12 were with DM. Glucose, C-Reactive protein (CRP), HbA1C, and Homeostasis Model Assessment Insulin Resistance (HOMA-IR) values were compared at the beginning and end of treatment. Results: In repeated measurements, there was a statistically significant decrease in the mean fasting blood glucose levels in patients with DM. Patients without DM also showed a reduction in the mean fasting blood glucose levels in repeated measurements, but this decrease was not statistically significant. There was a statistically significant decrease in the mean C-peptide level in repeated measurements in patients with DM and the mean insulin level in repeated measurements in patients without DM. There was a statistically significant decrease in the HOMA-IR values calculated in repeated measurements in patients with and without DM.Conclusion: In our study, insulin resistance decreased in pa tients receiving HBO2 therapy. The fact that this decrease was also shown in patients without DM strengthens the idea that this decrease is related to HBO2 therapy. Further research is needed to gain a more comprehensive understanding of the therapeutic potential of HBO2 therapy in managing insulin resistance.